ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING PADA PERUSAHAAN GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2012-2014 - Widjaya, Kunthi; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2017)
This study aims to determine the factors that influence underpricing. The variables studied were earnings per share (EPS), debt to equity ratio (DER), underwriter reputation, auditor reputation, industry type. Which method used in this research is purposive sampling, obtained as many samples 47 companies out of a population of 77 companies. This research was conducted with using multiple linear regression analysis with a significance level of 5%.The results of the study concluded that earning per share (EPS) variable successfully demonstrated a negative influence on the current underpricing of shares Initial public offering, debt to equity ratio (DER) failed to show there is a negative influence on the level of underpricing, the reputation of the underwriter is not managed to show a positive influence on underpricing, reputation. The auditor failed to show a negative effect on underpricing, and industry type variables did not work out negative effect on underpricing.